Logistics supply chains and their application - Petreski, Drage T.; Iliev, Andrej P.; Gjurov, Lazar M.; Petreska, Aleksandra D. (Vojnotehnički glasnik / Military Technical Courier, 2014)
Logistics is a set of activities for planning and implementingthe relocation of materials. Since sources of raw materials, factories and outlets are not usually in the same locationit is therefore necessary to conduct a series of logistics activities for supplying products or services to end users. Logistics manages the flow of data from suppliers, movement of materials through various operations within the organization as well as the flow of materials to final customers. Integrating these logistics activities is performed through supply chains which provide opportunities for cost saving and offering better services to customers. The supply chains in the Macedonian Army are an important factor in the planning and implementation of logistics support.